Analisis Pola Asuh Orang Tua Di TK Daarul Jannah Pontianak Timur - Zulhijah, Winda; Herlina, Urai; Sukmawati, Ema (Universitas Palangka Raya, 2024)
Parenting is a process of guiding, educating, and disciplining carried out by parents on children to achieve independence by applying certain norms that exist in the family and society. The purpose of this study was to describe and determine the description of parenting patterns in Daarul Jannah Kindergarten, East Pontianak. By using descriptive quantitative method and the number of samples involved was 11 respondents. In this study there are also specific objectives of the description of parenting patterns, types of parenting patterns, factors of parenting patterns. Data collection techniques in this study are interviews, questionnaires and documentation studies. The results showed that the parenting pattern most widely applied by parents of children at Daarul Jannah Kindergarten, East Pontianka is democratic parenting 82%, this percentage is more than authoritarian parenting 57% and permissive parenting 43%, and there are also factors that are most prominent, namely environmental factors at home. From these results it can be concluded that democratic parenting is the parenting pattern most widely applied by parents of children at Daarul Jannah Kindergarten in East Pontianak with the most visible factor being environmental factors.